Empiryczna analiza kosztów upadłości polskich przedsiębiorstw - Strąk, Tomasz (Empirical Analysis of Bankruptcy Costs in Polish Companies, 2006)
The paper presents the results of the research of bankruptcy costs in micro and small enterprises in Poland. The research sample comprised 41 companies with an average asset value of 434,294.57 PLN. The companies went bankrupt in the period 1995-1999. Bankruptcy proceedings lasted on average 899 days. Bankruptcy costs in the analysed group of companies usually accounted for 50% of book value of assets as of the day of bankruptcy and approx. 60% of their market value (i.e. cash inflow to bankruptcy estate). The cash inflow to bankruptcy estate was mainly spent to cover bankruptcy cost (ca. 63%) and only in 37% to satisfy claims. The obligations of the bankrupt were satisfied on average in approx. 17%. Only in one enterprise bankruptcy costs did not exceed 10% of the cash inflow to bankruptcy estate, while in five companies they exceeded 90%. The trustee's remuneration represented approx. 11% of bankruptcy costs and 6% of cash inflow to bankruptcy estate
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 569-578